Perancangan Antarmuka Pengguna Website OPTIIK Fotografi Dan Desain FILKOM UB Menggunakan Metode Human Centered Design (HCD), Focus Group Discussion (FGD), Dan Software Usability Scale Questionnaire (SUS) - Ilham Maulana Ubaidillah; Fatwa Ramdani; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The policy demands regarding SKM (legal evidence or curriculum vitae) regarding various activities carried out by students and is part of a requirement listed by students during Semhas registration or Results in Seminar and also thesis examination registration from the Faculty of Computer Science Universitas Brawijaya (FILKOM UB ) request OPTIIK FILKOM UB to have information media to be better known, especially in the academic community of FILKOM UB who have interest in photography and design. In today's digital era, the use of the internet as an information medium has increased in users. The data is quoted from Statista's data, which shows internet users in Indonesia in 2018 were 95.2 million, growing 13% from 2017, which was 84 million users. 2019 is projected at 12.6% or 107.2 million users. Increase in internet users due to access to the internet using websites to find information. Departing from the problems that have been analyzed, this research will create a website design using the Human Centered Design (HCD) approach and the Focus Group Discussion (FGD) approach and the design results using the Software Usability Questionnaire (SUS). In addition to producing the results of the user interface design, this study will also explain the comparison of the results of the user design and the comparison of the results of the SUS test for that design as a consideration for the development of the OPTIIK FILKOM UB website.